(untitled) (Journal of Nepal Geological Society, 2000)
The main water supply pipeline of the Lalitpur District passes through the Bungmati Landslide, which occurs on soft fluvio-lacustrine sediments of the Kathmandu Valley. The landslide study was carried out during the two rainy seasons (i.e. in 1992 and 1993). In the landslide zone, the Lukundol Formation is overlain by the Chapagaon Formation. The Lukundol Formation includes beds of peat, clayey diatomite, and fine sand, whereas the Chapagaon Formation consists mainly of gravel and sand. The detailed study of the landslide included engineering geological mapping, soil test, Rod Driving Test, and measurement of the displacement by the Vertical Wire Extensometer. The depth and total displacement of the slip surface were 6-7 m and 5- 25 cm, respectively. The main cause of sliding was the compositional difference between the Lukundol Formation and Chapagaon Formation. Percolation of water through the gravel beds resulted in the formation of pore water pressure and the development of the slip surface along the contact of the Lukundol Formation.